1995
DOI: 10.1152/jappl.1995.78.4.1547
|View full text |Cite
|
Sign up to set email alerts
|

Activity-wheel running attenuates suppression of natural killer cell activity after footshock

Abstract: We studied whether voluntary running in an activity wheel moderates splenic natural killer (NK) cell cytotoxicity after footshock. Young (50-day) male Fischer 344 rats were randomly assigned to 1) sedentary (n = 16) or 2) activity-wheel (n = 16) groups that each received controllable or uncontrollable footshock on 2 consecutive days or 3) a sedentary home-cage control group (n = 8). Spleens and trunk blood were collected 30 min after the second footshock session. Cytotoxicity was determined by a standard 4-h 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 0 publications
4
37
0
Order By: Relevance
“…This might be accomplished by investigating whether interventions aimed at increasing physical activity can buffer people from the immunologic changes associated with depression. Exercise serves this stress-buffering function in the rat immune response (33). It also will be important for future research to determine the health implications of the immunologic alterations described here and in previous studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This might be accomplished by investigating whether interventions aimed at increasing physical activity can buffer people from the immunologic changes associated with depression. Exercise serves this stress-buffering function in the rat immune response (33). It also will be important for future research to determine the health implications of the immunologic alterations described here and in previous studies.…”
Section: Discussionmentioning
confidence: 69%
“…To date, no research has considered whether physical activity might act as a mediator of the link between depression and immunity, despite evidence from the animal literature that exercise can provide a buffer against stress-induced downregulation of NKCC (33).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, studies have typically not shown a reliable effect of voluntary physical exercise on glucocorticoid responses to various acute stressor exposures in humans (Sothmann et al 1988) or animals (Dishman 1995(Dishman , 1998Fediuc et al 2006;Fleshner 2000). While it is the situations involving prolonged or repeated stressor exposures that are typically associated with physical and psychological illness, there has been little investigation into the potential for voluntary exercise to alter the way the body and brain respond to repeated stress.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, stressful events often precipitate and exacerbate psychiatric disorders such as depression and anxiety (Chorpita and Barlow, 1998;Kendler et al, 1999), and, compared with sedentary rats, several weeks of previous, voluntary access to running wheels results in dramatic alterations in immunological (Dishman et al, 1995;Fleshner, 2000;Avula et al, 2001;Moraska and Fleshner, 2001;Fleshner et al, 2002), neurochemical Dishman et al, 1997b;Soares et al, 1999;Greenwood et al, 2003), and behavioral (Dishman et al, , 1997aSolberg et al, 1999;Moraska and Fleshner, 2001) responses to stress.…”
Section: Introductionmentioning
confidence: 99%